What is hindering Chinese women from participating in combat sports? - Yike Li; Hansen Li; Dongchen Li; Xing Zhang; Zhenhuan Wang; Thomas Green; Guodong Zhang; Guodong Zhang (Frontiers Media S.A., 2024)
With the awakening of female consciousness, women's participation in sports has gradually gained autonomy and agency. However, Chinese women still face numerous restrictions in combat sports, hindering the development of this industry. Based on years of practice and research experience in the field, we summarize some general and specific issues, such as stigmatization and the constraints of traditional Chinese thinking. These issues need attention and consideration in the pursuit of gender equality in sports in the future.